2015
DOI: 10.1021/acsnano.5b03125
|View full text |Cite
|
Sign up to set email alerts
|

Self-Correcting Process for High Quality Patterning by Atomic Layer Deposition

Abstract: Nanoscale patterning of materials is widely used in a variety of device applications. Area selective atomic layer deposition (ALD) has shown promise for deposition of patterned structures with subnanometer thickness control. However, the current process is limited in its ability to achieve good selectivity for thicker films formed at higher number of ALD cycles. In this report, we demonstrate a strategy for achieving selective film deposition via a self-correcting process on patterned Cu/SiO2 substrates. We em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 39 publications
1
94
0
Order By: Relevance
“…Previous studies have achieved area selective deposition of thin films using methods such as relying on inherent selectivity differences between different surface materials, choosing precursors that enhance or delay the growth on one surface versus another, using an unreactive polymer film as a blocking layer in the regions where ALD is not desired or precursor infiltration in polymers . However, more commonly, the surface of the substrate is chemically modified with self‐assembled monolayers (SAMs) . These organic monolayer films form spontaneously on solid surfaces and are important in the fabrication of micro‐ and nanostructures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have achieved area selective deposition of thin films using methods such as relying on inherent selectivity differences between different surface materials, choosing precursors that enhance or delay the growth on one surface versus another, using an unreactive polymer film as a blocking layer in the regions where ALD is not desired or precursor infiltration in polymers . However, more commonly, the surface of the substrate is chemically modified with self‐assembled monolayers (SAMs) . These organic monolayer films form spontaneously on solid surfaces and are important in the fabrication of micro‐ and nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Toward AS‐ALD, different studies have shown promising results both in 2D and 3D by using SAMs to passivate the surface in the regions where ALD is not desired. For example, octadecylphosphonic acid (ODPA) has been used to direct area selective ALD of ZnO and Al 2 O 3 on metal/metal oxide patterns . Selective deposition of Pt, HfO 2 , and ZrO 2 has been demonstrated on SiH/SiO 2 patterns by protecting the surfaces using alkylsilane and alkyl monolayers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, octadecylphosphonic acid has been employed as an area selective resist layer to protect Cu for the effective deposition of ZnO using ALD or polyurea with MLD . The process was subsequently adapted with a selective etching step that allows for a “self‐correcting” strategy . Other ASD studies report using stable polymers such as poly(methyl methacrylate), poly(vinyl pyrrolidone), polyimide, and poly(methacrylamide) as mask layers to prevent ALD deposition.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Ideal ALD processes are based on self-limiting surface reactions in which the film nucleation critically relies on chemical interactions between gaseous precursor molecules and the solid substrate surface, providing an attractive opportunity for performing selective deposition via chemical surface modifications. 8 The rapidly progressing AS-ALD literature concentrates entirely on oxides and metals either via area-deactivated, [9][10][11][12][13][14][15][16] area-activated, [17][18][19][20] or inherent surface selectivity 21,22 approaches. Selective deposition recipes for nitride materials are however still missing, mainly due to the need for nitrogen plasma coreactants, which enable the nitrogen incorporation at reduced self-limiting growth temperatures.…”
Section: Introductionmentioning
confidence: 99%